“Kevin and Mattéo”, “those Little Angels”…: A Few Examples of Semantic Re-parameterizations, between Interdiscursive Echoes and Metadiscursive Work - Seoane, Annabelle (Verbum, 2024)
‘Kevin and Mattéo’, ‘imported product’, ‘community of Untouchables’, ‘piece of cloth’, ‘a chance’... Using the Figaro forum in 2023 (a French national newspaper) as a starting point, and from a discourse analysis perspective rooted in enunciation and semantics, the study examines the way in which certain lexical items are extracted from their usual meanings to be misappropriated in order to designate immigrants or refugees on French soil and thus condenses a political rejection of Muslims in particular and more generally of the current government. Through the interplay of semantic or pragma-enunciative adjustments and a fundamentally dialogical enunciation, the new setting here articulates an informative aim of deciphering with an intention of disqualification based on stereotyping and stigmatization. It is then a question for the enunciator of implementing a conniving logic of de-/re-construction of meaning.
Keywords: enunciation; semantic adjustments; hate speech; stereotypin; stigmatization